2013
DOI: 10.1007/s00268-013-2370-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Perioperative and Long‐term Outcomes of Total and Proximal Gastrectomy for Early Gastric Cancer: A Multi‐institutional Retrospective Study

Abstract: Three surgical procedures for U-EGC did not result in differences in weight loss, but PG-EG and PG-JI were better than TG-RY according to some nutritional markers. In U-EGC, where patients are expected to have long survival times, PG-EG and PG-JI should be used rather than TG-RY.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
76
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 37 publications
2
76
1
4
Order By: Relevance
“…While there is still lack of agreement that PG-JI or PG-DT can replace TG-RY, PG-JI and PG-DT, as function-preserving surgery, do have several advantages over TG-RY [3,[6][7][8][12][13][14][15][16][17]. First, the remnant stomach offers significantly increased food intake volume and better QOL for patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While there is still lack of agreement that PG-JI or PG-DT can replace TG-RY, PG-JI and PG-DT, as function-preserving surgery, do have several advantages over TG-RY [3,[6][7][8][12][13][14][15][16][17]. First, the remnant stomach offers significantly increased food intake volume and better QOL for patients.…”
Section: Discussionmentioning
confidence: 99%
“…PG-JI, with its reduction in postoperative body weight loss compared to TG-RY, contributes to better QOL for patients and thus is well adopted [8]. In addition, the incidence of esophageal reflux was reported significantly lower after PG-JI compared to PG-EG [6,9]. Nevertheless, Tokunaga's questionnaire showed that after PG-JI, the interposed jejunum might prevent the smooth passage of food, leading to the abdominal discomfort after meals [10].…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Among the 3921 individuals comprising the base population, 204 of 300 patients with T1 upper-third gastric cancer underwent proximal gastrectomy. Although LNs lying along the right gastric and right gastroepiploic vessels are not dissected, survival outcome after proximal gastrectomy performed for early upper-third gastric cancer is known to be comparable with that after total gastrectomy [17,18]. Several reports have demonstrated that the occurrence of metastasis from upper-third gastric cancer to LNs at the no.…”
Section: Discussionmentioning
confidence: 99%
“…Although proximal gastrectomy is generally thought to offer advantages over conventional total gastrectomy in terms of maintenance of food intake volume [21][22][23] and postoperative nutrition status [17], reflux esophagitis or Fig. 3 a, b Mapping of the primary tumors with single-site metastasis to the no.…”
Section: Discussionmentioning
confidence: 99%